The teahouse under socialism the decline and renewal of public life in Chengdu, 1950-2000 - Wang, Di 1956- (Cornell University Press, 2018)
To understand a city fully, writes Di Wang, we must observe its most basic units of social life. In The Teahouse under Socialism, Wang does just that, arguing that the teahouses of Chengdu, the capital of Sichuan Province, are some of the most important public spaces―perfect sites for examining the social and economic activities of everyday Chinese.